A TEMPOL and rapamycin loaded nanofiber-covered stent favors endothelialization and mitigates neointimal hyperplasia and local inflammation - Rui Wang; Jian Lu; Jiasheng Yin; Han Chen; Hongmei Liu; Fei Xu; Tongtong Zang; Rende Xu; Chenguang Li; Yizhe Wu; Qilin Wu; Xiang Fei; et al. (Bioactive Materials, 2023)
An increased level of reactive oxygen species (ROS) plays a major role in endothelial dysfunction and vascular smooth muscle cell (VSMC) proliferation during in-stent thrombosis and restenosis after coronary artery stenting. Herein, we report an electrospun core-shell nanofiber coloaded with 4-hydroxy-2,2,6,6-tetramethylpiperidine 1-oxyl (TEMPOL) and rapamycin (RAPA) that correspondingly serves as an ROS scavenger and VSMC inhibitor. This system has the potential to improve the biocompatibility of current drug-eluting stent (DES) coatings with the long-term and continuous release of TEMPOL and rapamycin. Moreover, the RAPA/TEMPOL-loaded membrane selectively inhibited the proliferation of VSMCs while sparing endothelial cells (ECs). This membrane demonstrated superior ROS-scavenging, anti-inflammatory and antithrombogenic effects in ECs. In addition, the membrane could maintain the contractile phenotype and mitigate platelet-derived growth factor BB (PDGF-BB)-induced proliferation of VSMCs. In vivo results further revealed that the RAPA/TEMPOL-loaded covered stents promoted rapid restoration of vascular endothelium compared with DES and persistently impeded inflammation and neointimal hyperplasia in porcine models.